2013
DOI: 10.1007/s11852-013-0246-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relatedness of the mangrove Rhizophora mangle L. (Rhizophoraceae) using amplified fragment polymorphism (AFLP) among locations in Florida, USA and the Caribbean

Abstract: Rhizophora mangle L. is a widespread mangrove species in the Western Hemisphere. Mangrove habitat loss and their importance to coastal and reef ecosystems make greater understanding of their genetic structure useful for conservation and management. An amplified fragment polymorphism (AFLP) analysis was performed on samples from Florida and the Caribbean to discover the genetic structure present. R. mangle had variable genetic diversity not related to latitude; P ranged 7 %-92 %. Some other factor, perhaps huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…Mangrove populations are very small at the range edge, which can limit adaptation even in the face of strong selection (Bridle & Vines 2007). Mangrove propagules can also be dispersed broadly via ocean waters and remain viable after long periods of flotation (Triest 2008;Albrecht et al 2013), which may allow maladaptive gene flow from centre populations (Bridle & Vines 2007). Additionally, mangroves already tolerate highly stressful conditions, including high salinity and anaerobic soils, which may impose strong selective pressures (Etterson 2001) and dampen the ability of mangroves to evolve in response to other selective pressures such as freeze stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove populations are very small at the range edge, which can limit adaptation even in the face of strong selection (Bridle & Vines 2007). Mangrove propagules can also be dispersed broadly via ocean waters and remain viable after long periods of flotation (Triest 2008;Albrecht et al 2013), which may allow maladaptive gene flow from centre populations (Bridle & Vines 2007). Additionally, mangroves already tolerate highly stressful conditions, including high salinity and anaerobic soils, which may impose strong selective pressures (Etterson 2001) and dampen the ability of mangroves to evolve in response to other selective pressures such as freeze stress.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variability of mangroves species, particularly that of R. mangle , began to be studied with the use of biochemical markers by Dodd, Rafii, Fromard, and Blasco (), and in the past decade with DNA molecular markers by Arbeláez‐Cortes, Castillo‐Cárdenas, Toro‐Perea, and Cárdenas‐Henao (). Recently, several studies (the majority of them using microsatellite molecular markers) have reported a great genetic variability within populations of R. mangle in America (Albrecht, Kneeland, Lindroth, & Foster, ; Arbeláez‐Cortes et al, ; Bruschi et al, ; Cerón‐Souza et al, ; Cerón‐Souza, Bermingham, McMillan, & Jones, ; Pil et al, ). However, none of these studies have considered the physiognomic type of mangrove in their sampling plan.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies (the majority of them using microsatellite molecular markers) have reported a great genetic variability within populations of R. mangle in America (Albrecht, Kneeland, Lindroth, & Foster, 2013;Arbeláez-Cortes et al, 2007;Bruschi et al, 2013;Cerón-Souza et al, 2015;Cerón-Souza, Bermingham, McMillan, & Jones, 2012;Pil et al, 2011). However, none of these studies have considered the physiognomic type of mangrove in their sampling plan.…”
mentioning
confidence: 99%
“…The hydrologic, oceanographic and geophysical attributes key to maintaining the integrity of the proposed nomination include the consistently high water quality due to the combined effects of continuous water circulation and fortuitous geological and meteorological factors which restrict sediment and freshwater stressors. With an oasis of marine life in relatively barren tropical ocean waters positioned at a critical upstream position within the Tropical Western Atlantic Province, the proposed nomination has played a key role in the process of reproduction, dispersal and colonization by marine organisms in the Caribbean, and continue to do so today (Albrecht et al 2013, Baldwin et al 2014. As reefs in the region continue to decline rapidly (Jackson et al 2013), the proposed nomination where partial reef recovery can be documented in certain areas, represents the last best hope for regional coral reefs.…”
Section: Description Of Valuesmentioning
confidence: 99%
“…It is an important bird area for at least 29 species of migratory waterbirds (Debrot et al 2012a). Finally, it is also a hotspot for genetic diversity in the mangrove Rhizophoa mangle, the most prominent mangrove of the Caribbean (Albrecht et al 2013).…”
Section: Key Biodiversity Areasmentioning
confidence: 99%